STRATEGI PENINGKATAN KUALITAS PELAYANAN DI LABORATORIUM RUMAH SAKIT UMUM BAHTERAMAS PROVINSI SULAWESI TENGGARA TAHUN 2023 - Mita; Fajar Kurniawan; Fitri Kurniawati (CV. ALIM'SPUBLISHING, 2023)
The purpose of this research is to improve the quality of service strategy in the laboratory of the Umu Bahtermas Hospital, Southeast Sulawesi Province. This type of research is quantitative by describing the results of Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The sample in this study were 95 respondents. Research using SPSS software and Windows software. The results of the analysis show that in the Importance Performance Analysis (IPA) results there are 4 attributes that need to be improved, namely: The laboratory provides a place for washing hands, Timeliness of service (time of registration), laboratory personnel respond patiently to each patient's questions and officers are able to provide solutions to problems experienced by patients. In the analysis of the Customer Satisfaction Index(CSI) it is known that the level of patient satisfaction is 82.75 with the category of Very Satisfied CSI criteria. Bahteramas General Hospital in Southeast Sulawesi Province pays more attention to the existing facilities in the laboratory and improves the quality of good service to patients.